Is the “end‐of‐study guess” a valid measure of sham blinding during transcranial direct current stimulation? - Turner, Christopher; Jackson, Catherine; Learmonth, Gemma (The European journal of neuroscience, 2021)
Studies using transcranial direct current stimulation (tDCS) typically incorporate a fade‐in, short‐stimulation, fade‐out sham (placebo) protocol, which is assumed to be indistinct from a 10–30 min active protocol on the scalp. However, many studies report that participants can dissociate active stimulation from sham, even during low‐intensity 1 mA currents. We recently identified differences in the perception of an active (10 min of 1 mA) and a sham (20 s of 1 mA) protocol that lasted for 5 min after the cessation of sham. In the present study we assessed whether delivery of a higher‐intensity 2 mA current would exacerbate these differences. Two protocols were delivered to 32 adults in a double‐blinded, within‐subjects design (active: 10 min of 2 mA, and sham: 20 s of 2 mA), with the anode over the left primary motor cortex and the cathode on the right forehead. Participants were asked “Is the stimulation on?” and “How sure are you?” at 30 s intervals during and after stimulation. The differences between active and sham were more consistent and sustained during 2 mA than during 1 mA. We then quantified how well participants were able to track the presence and absence of stimulation (i.e. their sensitivity) during the experiment using cross‐correlations. Current strength was a good classifier of sensitivity during active tDCS, but exhibited only moderate specificity during sham. The accuracy of the end‐of‐study guess was no better than chance at predicting sensitivity. Our results indicate that the traditional end‐of‐study guess poorly reflects the sensitivity of participants to stimulation, and may not be a valid method of assessing sham blinding. We quantified how well participants were able to track the presence and absence of a tDCS current (i.e. their sensitivity), using cross‐correlations. Current strength was a good classifier of sensitivity (higher for 2mA than 1mA), but the accuracy of their end‐of‐study guess was no better than chance at predicting sensitivity. The traditional end‐of‐study guess method poorly reflects the sensitivity of participants to stimulation, and may not be a valid method of assessing sham blinding.